Fluorodeoxyglucose-positron emission tomography integrated with computed tomography in suspected recurrent cervical cancer - Stojiljković Milica; Artiko Vera (Medicinski Podmladak)
Carcinoma of the uterine cervix represents the fourth most common malignant tumor and the fourth leading cause of mortality from cancer in females, and approximately one third of women with cervical carcinoma diagnosis will develop relapse. In follow-up and suspicion of recurrence of cervical cancer, various imaging modalities such as computed tomography (CT), magnetic resonance imaging (MRI) and positron emission tomography/computed tomography (PET/CT) can be used. However, the role of PET/CT is constantly increasing in these patients and the latest National Comprehensive Cancer Network (NCCN) guideline Version 1.2023 recommends PET/CT as the imaging method of choice in follow-up of patients with disease stage II or higher, and in suspicion of recurrent or metastatic disease. PET/ CT shows higher sensitivity and specificity than conventional imaging in suspected recurrent cervical cancer, particularly in the evaluation of distant recurrent sites. An additional benefit of PET/CT in these patients is its impact on treatment management in approximately half of them. Also, PET/CT has a prognostic role in progression-free and overall survival, and patients with positive PET/CT for recurrence have significantly worse prognosis.